Penegakan Pasal 27 Ayat (3) Undang-Undang Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Makkasau, Edi Suryanto; Mirzana, Hijrah Adhyanti; Muin, Audyna Mayasari (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze legal factors and law enforcement factors in the enforcement of Article 27 paragraph (3) of the ITE Law. This study used the type of empirical legal research. The data sources were in the form of primary data and secondary data. The data analysis technique used descriptive qualitative. The study results showed that the legal factors that influence the application of Article 27 paragraph (3), namely the lex certa element in the formulation of the offense, had not been fulfilled. The explanation of the phrase without rights and transmitting was not in line with Articles 310 and 311 of the Criminal Code. The ideal law enforcement had not been realized in the application of Article 27 paragraph (3) because the indicators of the principle of legality and clarity of phrases in the law had not been fulfilled, and there were still quality, quantity, and coordination constraints from law enforcement officers.